2014
DOI: 10.3141/2402-04
|View full text |Cite
|
Sign up to set email alerts
|

Turboroundabouts

Abstract: A "turboroundabout" is a variation of the conventional multilane roundabout in which spiral road markings and raised lane dividers force drivers to follow a specific path according to their intended destination. This geometry eliminates weaving and cut-in conflicts by guiding drivers continuously from entry to exit. Turboroundabouts were conceived with the main aim of improving safety, but their practical benefits are relatively unknown. Likewise, the few existing studies on turboroundabouts do not allow defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…The transformation of a conventional two-lane roundabout into a turbo-roundabout resulted in a reduction of the frequency of potential accidents between 40 and 50%, as there is a positive linear correlation between the potential number of accidents and the traffic volume. Also Vasconcelos et al (2014) found benefits in terms of safety. Using microsimulation techniques and SSAM software (Surrogate Safety Assessment Model), a comparative performance analyzes between single-lane roundabouts, multi-lane roundabouts and turbo-roundabouts was developed.…”
Section: State Of the Artmentioning
confidence: 92%
See 2 more Smart Citations
“…The transformation of a conventional two-lane roundabout into a turbo-roundabout resulted in a reduction of the frequency of potential accidents between 40 and 50%, as there is a positive linear correlation between the potential number of accidents and the traffic volume. Also Vasconcelos et al (2014) found benefits in terms of safety. Using microsimulation techniques and SSAM software (Surrogate Safety Assessment Model), a comparative performance analyzes between single-lane roundabouts, multi-lane roundabouts and turbo-roundabouts was developed.…”
Section: State Of the Artmentioning
confidence: 92%
“…In recent studies carried out by Vasconcelos et al (2012Vasconcelos et al ( , 2014, the main differences affecting the capacity estimates, and based on the Hagring formula are shown and it was concluded: (i) the capacity of the major road entries of turbo-roundabouts are always lower than the conventional roundabouts because the opposite traffic flow is only concentrated in one lane of the circulatory carriageway; (ii) the relative performance of turbo-roundabouts decreases with increasing demand in the main direction, reaching capacity losses of 40%; (iii) in secondary entries, turbo-roundabouts ensure better performance, but only for specific demand scenarios, especially with very high proportion of right turns (above 60%). These results show the importance of the analysis, as the performance of the turbo-roundabout undeniably depends on the traffic volume and on the traffic distribution.…”
Section: State Of the Artmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies conducted on turbo roundabouts [8][9][10][11][12][13][14][15] were mainly based on evaluation of their performances (capacity, delays), and environmental, economic and safety benefits, in regard to single-lane, standard multilane, flower and target roundabouts. Turbo roundabout geometric design was considered in a number of other studies [1, 16÷19], which were generally focused on analysis of Dutch turbo roundabout geometry and presentation of new design approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1). These additional lanes can also be installed at conventional roundabouts and at more recently designed roundabouts, such as turbo-roundabouts [5][6][7][8], C-roundabouts [9], target-roundabouts [10] and flower-roundabouts (the layout of the latter is just characterized by bypass lanes at each arm [11]). Right-turn bypasses increase conflict points between vehicles and between vehicles and pedestrians/cyclists [12][13][14][15] and, to a modest extent, the number of accidents [16].…”
Section: Introductionmentioning
confidence: 99%